The Concept of Muhibah in Nation-Building in Malaysia: the Challenges and Prospects - Norhasniah Wan Husin, Wan; Ibrahim, Haslina (International Journal of Engineering and Technology, 2018)
This article deliberated on the concept of muhibah and its application as a means to foster harmony in the Malaysian pluralistic society comprising mainly the Malays, Chinese and Indians. Given the multiracial, multicultural and multireligous background, the study acknowledges the need to protect one’s heritage and cultural traits which are necessarily connected to the question of right and freedom as the Malaysian citizen. The questions at hands, how is it possible to inculcate muhibah in the face of multiple claims to right and freedom. The article will therefore focus on the two issues pertain to right which are the right to freedom of religion and the right to language. The analysis is qualitative in nature and it relied upon library research for data collection. The article adopts textual analysis method for data analysis. The findings show that despite its historical relevance and practicality, implementing muhibah has been very challenging in Malaysia. This is due the pressing demand from particular ethnic and religion, to preserving their cultural trait. It is therefore concluded that the success of muhibah is a reciprocal process. It can be achievable if every ethnic group in Malaysia have trust and respect for the national policy such as muhibah and therefore willing to work together in realizing the policy.
Keywords: Muhibah; Nation-building; Plural Society; Malaysia